2010
DOI: 10.1111/j.1365-294x.2010.04797.x
|View full text |Cite|
|
Sign up to set email alerts
|

The making of a rapid plant invader: genetic diversity and differentiation in the native and invaded range of Senecio inaequidens

Abstract: To become invasive, exotic species have to succeed in the consecutive phases of introduction, naturalization, and invasion. Each of these phases leaves traces in genetic structure, which may affect the species' success in subsequent phases. We examined this interplay of genetic structure and invasion dynamics in the South African Ragwort (Senecio inaequidens), one of Europe's fastest plant invaders. We used AFLP and microsatellite markers to analyze 19 native African and 32 invasive European populations. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 74 publications
3
101
1
Order By: Relevance
“…Moreover, a review of genetic variation in 80 invasive species (including 18 plant species) has shown that some loss of genetic variation is associated with most invasions (Dlugosch and Parker 2008a). In contrast, Wares et al (2005) found little evidence for a loss of genetic variation within populations of introduced/ invasive animal species, and there is increasing evidence for a similar pattern emerging in recent plant studies (Marrs et al 2008a;Chun et al 2009;Doorduin et al 2010;Lachmuth et al 2010;Pairon et al 2010). Indeed, in some plant species, genetic variation appears to have increased during invasions (Neuffer and Hurka 1999;Genton et al 2005;Lavergne and Molofsky 2007;Alexander et al 2009).…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, a review of genetic variation in 80 invasive species (including 18 plant species) has shown that some loss of genetic variation is associated with most invasions (Dlugosch and Parker 2008a). In contrast, Wares et al (2005) found little evidence for a loss of genetic variation within populations of introduced/ invasive animal species, and there is increasing evidence for a similar pattern emerging in recent plant studies (Marrs et al 2008a;Chun et al 2009;Doorduin et al 2010;Lachmuth et al 2010;Pairon et al 2010). Indeed, in some plant species, genetic variation appears to have increased during invasions (Neuffer and Hurka 1999;Genton et al 2005;Lavergne and Molofsky 2007;Alexander et al 2009).…”
Section: Introductionmentioning
confidence: 90%
“…An alternative explanation might be that a more invasive strain of S. madagascariensis was subsequently introduced around the time of lag phase break, and was then able to spread more effectively than the resident S. madagascariensis genotypes present at that time. This second scenario has been supported in a study of the European invasion of S. inaequidens , where historical and molecular data were combined to reveal that a 70 year lag phase in Bremen, Germany, was broken by the arrival of additional native range genotypes via a different invasion route, which ‘overran’ the more slowly expanding resident population [35]. Recent work examining the dispersal ability of S. madagascariensis populations at the centre verses edges of its range in Australia have not found any significant differences [36], however this does not preclude superior dispersal ability across the range in Australia when compared to native or historically invasive populations.…”
Section: Introductionmentioning
confidence: 92%
“…Several other studies already suggested that invasiveness may be the result of different combinations of particular functional traits such as high reproductive success [46], dispersal ability [47], increased size or competitive ability [12]. Moreover, multiple introductions, environmental preadaptation and high gene flow along invasion routes also contributed to the success of this rapid Senecio invader [48]. …”
Section: Herbivore Impacts Throughout the Life Cyclementioning
confidence: 99%